Chemical Characteristics of Waru Leaf (Hibiscus tiliaceus) As Food Packaging Material - Angela Firdausa Alif Iskandar; Umar Santoso; Supriyadi Supriyadi (Indonesian Food and Nutrition Progress, 2023)
Waru leaf (Hibiscus tilaceus) is commonly used as a traditional food packaging material in Indonesia. Waru leaf is known to contain bioactive components with antioxidant and antimicrobial activity. This research aimed to determine the chemical properties of waru leaf of various maturity levels and provide information on the potency of leaf extract that can be used as active packaging additive. The chemical properties include fatty acids, volatile compounds, antioxidant activity, and total phenolic content. It was discovered that both the young and mature waru leaf contained 4 types of fatty acids: predominantly linoleic acid and linolenic acid. In the young waru leaf, the primary volatile compounds were acids, with cis-vaccenic acid (21%) and glycidyl palmitate comprising (16.8%). As for the mature leaf, the main volatile compounds were acids and esters, with glycidyl oleate at (18.52%), glycidyl palmitate (12.28%), and Decocanoic acid, 3-hydroxy- (7.85%). The crude methanol extract was fractionated with hexane, ethyl acetate, and butanol to analyze bioactive compounds. The highest antioxidant activity was found in ethyl acetate fraction with an average of %Radical Scavenging Activity (%RSA) of 36.25% on the young waru leaf and 29.92% on the mature waru leaf. The ethyl acetate fraction had the highest total phenolic content of 164.66 mg GAE/g and 146.50 mg GAE/g for young and mature waru leaves, respectively. The result shows that waru leaf extract is a potential ingredient for developing active packaging.